Removal of humic and tannic acids by adsorption-coagulation combined systems with activated biochar - Jung, C.; Phal, N.; Oh, J.; Chu, K.H.; Jang, M.; Yoon, Y. (Elsevier, 2015)
Despite recent interest in transforming biomass into bio-oil and syngas, there is inadequate information on the compatibility of byproducts (e.g., biochar) with agriculture and water purification infrastructures. A pyrolysis at 300 degrees C yields efficient production of biochar, and its physicochemical properties can be improved by chemical activation, resulting in a suitable adsorbent for the removal of natural organic matter (NOM), including hydrophobic and hydrophilic substances, such as humic acids (HA) and tannic acids (TA), respectively. In this study, the adsorption affinities of different HA and TA combinations in NOM solutions were evaluated, and higher adsorption affinity of TA onto activated biochar (AB) produced in the laboratory was observed due to its superior chemisorption tendencies and size-exclusion effects compared with that of HA, whereas hydrophobic interactions between adsorbent and adsorbate were deficient. Assessment of the AB role in an adsorption-coagulation hybrid system as nuclei for coagulation in the presence of aluminum sulfate (alum) showed a synergistic effect in a HA-dominated NOM solution. An AB-alum hybrid system with a high proportion of HA in the NOM solution may be applicable as an end-of-pipe solution. (C) 2015 Elsevier B.V. All rights reserved.